2009
DOI: 10.1086/603583
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Teachers’ Didactic Strategies: Examining the Comparative Potential of Low Inference Generic Descriptors

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The consensus seems to be that teachers employ pedagogical strategies which, through repeated enactment, are not only typical of a country's lessons but also beneath their consciousness (Cogan & Schmidt, 1999). This sense of typicality has found confirmation in Andrews' research in which mathematics teachers from four European countries have been observed to behave, at least as far as seven generic learning outcomes and ten generic didactic strategies are concerned, in ways that align them closely with their national colleagues and distinguish them from their overseas colleagues (Andrews, 2007b(Andrews, , 2009a(Andrews, , 2009b. Explanations suggest that cultures "shape the classroom processes and teaching practices within countries, as well as how students, parents and teachers perceive them" (Knipping, 2003, p. 282).…”
Section: Mathematical Knowledge In Teaching: a Culturally-located Modelmentioning
confidence: 75%
See 4 more Smart Citations
“…The consensus seems to be that teachers employ pedagogical strategies which, through repeated enactment, are not only typical of a country's lessons but also beneath their consciousness (Cogan & Schmidt, 1999). This sense of typicality has found confirmation in Andrews' research in which mathematics teachers from four European countries have been observed to behave, at least as far as seven generic learning outcomes and ten generic didactic strategies are concerned, in ways that align them closely with their national colleagues and distinguish them from their overseas colleagues (Andrews, 2007b(Andrews, , 2009a(Andrews, , 2009b. Explanations suggest that cultures "shape the classroom processes and teaching practices within countries, as well as how students, parents and teachers perceive them" (Knipping, 2003, p. 282).…”
Section: Mathematical Knowledge In Teaching: a Culturally-located Modelmentioning
confidence: 75%
“…This provides a basis for evaluating the effectiveness of the tripartite curriculum as a complementary framework to the Shulman-related model discussed above. To facilitate this process, the percentages, drawn from Andrews (2009aAndrews ( , 2009b, of all Flemish and Hungarian episodes coded for each of the generic learning outcomes and didactic strategies are presented in Table 1, alongside the same summary statistics for the episodes of each of the two teachers. Details of the codes are beyond this chapter, although working definitions can be seen in Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations